2022
DOI: 10.1039/d1en00941a
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous UV disinfection aided by ZnO/Al2O3 composites for inhibiting antibiotic resistant bacteria photoreactivation and gene recovery

Abstract: Photoreactivation has limited antibiotic resistant bacteria (ARB) and gene (ARG) reduction by ultraviolet (UV) heterogeneous disinfection. ZnO/Al2O3 particles where ZnO length ranged around 400 nm was synthesized by template-hydrothermal method....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…20,22,23 As a semiconductor material, ZnO nanoparticles have significant photocatalytic activity and can generate large amounts of reactive oxygen species (ROS) under irradiation by visible and ultraviolet (UV) light to efficiently inactivate bacteria. [24][25][26] In comparison with conventional-scale ZnO nanoparticles, ZnO quantum dots (ZnO QDs) show higher plant transport efficiency, 27,28 higher photocatalytic efficiency and higher antibacterial activity. 29,30 ZnO QDs can effectively control plant bacterial diseases, such as bacterial fruit blotch disease, 31 citrus canker disease and citrus huanglongbing disease, 28 mainly by the generation of ROS and the release of Zn 2+ during the binding of ZnO QDs and bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,22,23 As a semiconductor material, ZnO nanoparticles have significant photocatalytic activity and can generate large amounts of reactive oxygen species (ROS) under irradiation by visible and ultraviolet (UV) light to efficiently inactivate bacteria. [24][25][26] In comparison with conventional-scale ZnO nanoparticles, ZnO quantum dots (ZnO QDs) show higher plant transport efficiency, 27,28 higher photocatalytic efficiency and higher antibacterial activity. 29,30 ZnO QDs can effectively control plant bacterial diseases, such as bacterial fruit blotch disease, 31 citrus canker disease and citrus huanglongbing disease, 28 mainly by the generation of ROS and the release of Zn 2+ during the binding of ZnO QDs and bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of Zn, ZnO nanomaterials are now widely used as plant fertilisers and human food additives 20,22,23 . As a semiconductor material, ZnO nanoparticles have significant photocatalytic activity and can generate large amounts of reactive oxygen species (ROS) under irradiation by visible and ultraviolet (UV) light to efficiently inactivate bacteria 24–26 . In comparison with conventional‐scale ZnO nanoparticles, ZnO quantum dots (ZnO QDs) show higher plant transport efficiency, 27,28 higher photocatalytic efficiency and higher antibacterial activity 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…At present, various methods, including plasma, combustion, and catalytic hydrolysis, have been developed for the decomposition methods of CF 4 . Among them, catalytic hydrolysis is regarded as a promising method owing to its capability of high decomposition efficiency and large gas flux. Al-based materials with abundant acidic sites are the most used catalysts in decomposition of CF 4 . Song et al reported that the more the Lewis acid sites on the surface of Al-based catalysts, the stronger the ability to decompose CF 4 . Zhang et al found that the strong Lewis acid site of unsaturated tricoordinated Al (Al III ) was the main active site for CF 4 decomposition, indicating that more Al III active sites represent higher CF 4 decomposition activity.…”
Section: Introductionmentioning
confidence: 99%